The evaluation of the Merdeka curriculum implementation in elementary schools - Suci, Fahma; Irsyad; Sulastri; Kadri, Hanif Al (Indonesian Research Journal in Education |IRJE|, 2025)
The research aims to determine the extent to which the implementation of the Merdeka curriculum in public elementary schools is seen from the aspects of teacher understanding, learning planning, mastery of teaching tools, strategies and approaches, teacher readiness for learning outcome assessment, knowing the challenges and obstacles, and the impacts caused on the learning process and the quality of education (student learning outcomes) in Pasaman, West Pasaman Regency. This research is an evaluation study that utilizes Stake's Countenance model. The research occured at two elementary schools, specifically SDN 30 Pasaman and SDN 21 Pasaman. The results of the research showed that teacher understanding of the implementation of the Merdeka curriculum, learning planning, mastery of teaching tools, strategies and approaches, teacher readiness for learning outcome assessment and challenges and obstacles, and the impacts caused on the learning process at SDN 30 Pasaman were by the standards issued by the Ministry of Education and Culture regarding the implementation of the Merdeka curriculum. However, at SDN 21 Pasaman, there is still a need to improve teacher competence and the condition of school infrastructure and improve the quality of learning implementation. This need for improvement is due to the significant damage to school infrastructure caused by natural disasters and the teachers' insufficient pedagogical and professional competence.